Isu Kontemporer Pendidikan Islam dalam Peningkatan Kurikulum (Implementasi Kurikulum Merdeka di Madrasah) - Encep Syarifudin; Agus Gunawan; A.Hendrid Suko Prastyono; Puji Lestari (Jurnal Administrasi Pendidikan Islam, 2023)
Islamic education must be taught to the younger generation, especially Muslims, so they grow to be good members of society. When it comes to issues such as curriculum development and education renewal, learning studies play an important role to be carried out to raise the effectiveness of Islamic education in Islamic educational institutions such as Madrasah. This research was conducted using the library research method (Library Research), curriculum development is one of the contemporary issues in Islamic education, the question arises whether contemporary issues of Islamic education in the implementation of independent curriculum activities in madrasah are needed. This paper also explains what and how scope the implementation of the independent curriculum is implemented in Madrasah and the renewal of the curriculum imposed by the government should be able to make Madrasah more independent in management and learning. The increase of activity and creativity of students in groups could build a sense of working together according to the indicators in the pancasila profile on independent curriculum.